Technological Innovation in the Olive Oil Production Chain 2019
DOI: 10.5772/intechopen.81390
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Extraction Technologies in Olive Oil Production

Abstract: In the field of olive oil extraction, current scientific research has focused on improving quality, paying particular attention to optimizing the efficiency of extraction and reducing the duration of the process. Recently, studies have been conducted to improve the traditional malaxation process and obtain positive effects on both oil production and consumption. With these aims, emerging technologies including microwave (MW), pulsed electric field (PEF), and ultrasound (US) have been applied to conventional vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Techniques of Olea eurpaea L. [13][14][15] 5.1. Extraction techniques 13 1. Traditional Extraction Methods : The traditional method for extra virgin olive oil (EVOO) mechanical cold-press extraction involve three main processes: crushing, malaxation, and centrifugation.…”
Section: Extraction and Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques of Olea eurpaea L. [13][14][15] 5.1. Extraction techniques 13 1. Traditional Extraction Methods : The traditional method for extra virgin olive oil (EVOO) mechanical cold-press extraction involve three main processes: crushing, malaxation, and centrifugation.…”
Section: Extraction and Formulationmentioning
confidence: 99%
“…to be crucial to a Mediterranean diet, a great deal of research has been done on it to determine its origin and find evidence of adulteration and fraud. Numerous analytical methods, including as mid-infrared resonance (MIR), near-infrared resonance (NIR), and 1 H and 13 C nuclear magnetic resonance imaging (NMR) imaging, have been employed to evaluate the quality and look into oil adulteration. Other spectroscopic methods, like ultraviolet spectrometry, Fourier transform infrared (FTIR) spectroscopy, [48][49][50] fluorescence spectroscopy, Raman spectroscopy, and fluorescence spectroscopy, have a lot of potential for characterizing various olive oil samples from the perspective of organic substances and, consequently, detecting their adulteration.…”
Section: Extraction and Formulationmentioning
confidence: 99%
“…Olive trees are indigenous to Italy, Greece, Palestine, Syria, and many other surrounding countries [159]. The processing and extraction of olive oil has been traditionally carried out via mechanical methods which included crushing, malaxation, and centrifugation [160]. A reason that mechanical methods are still commonly used even in modern times is the lack of need for further refinement, as olive oil is safe for consumption directly after mechanical extraction [161].…”
Section: Olive Oilmentioning
confidence: 99%
“…A reason that mechanical methods are still commonly used even in modern times is the lack of need for further refinement, as olive oil is safe for consumption directly after mechanical extraction [161]. Olive oil extractions on an industrial scale have, in recent years, been adopting microwave, pulsed electric field, and ultrasound assisted olive oil extraction to increase the yield and quality of the extracted oil [160]. The sterol content of extra virgin olive oil was 319 mg/100 g [37].…”
Section: Olive Oilmentioning
confidence: 99%
“…It is reported that 40% of the world's production of olives (21 thousand tons in 2018) is destined for olive oil manufacturing. The edible oils are typically produced through a malaxation process, with a net yield reaching around 36% (Yüksel Aydar, 2019). Most of the wastes generated in such an approach are olive wood, leaves, cakes, almonds, pasta, and wastewater from the olive mill (Roselló‐Soto et al., 2015).…”
Section: Outlook On Agro‐food Wastes and By Products And Their Global...mentioning
confidence: 99%